Learning by outward and inward internationalization and the outward/inward innovativeness of firms in Poland - Maja Szymura-Tyc (International Journal of Management and Economics, 2021)
Many studies raise the issue of relationships between internationalization and innovativeness, linking them with firms' international competitiveness. However, very few of these studies focus on the influence of internationalization on innovativeness and regard the multifaceted nature of these two concepts. The study presented in this paper is based on a holistic approach to internationalization and innovativeness. It explores the influence of the outward (e.g. exporting, outward FDI) and inward (e.g. importing, inward FDI) internationalization on the outward (product and marketing) and inward (process and organizational) innovativeness of 274 firms in Poland, adopting formative variables and a correlations analysis. The key contribution of the research is that the outward internationalization is conducive to both the outward and inward innovativeness, while the inward internationalization supports only the inward innovativeness. It shows that learning by outward and inward internationalization supports innovativeness of firms, responsible for their international competitiveness. The findings might be unique for transition and emerging economies characterized with a low degree of internationalization and innovativeness, while the holistic approach is more universal, and might bring interesting results when applied to the research of highly advanced economies.
Keywords: M16; O30; L25; 650; outward-inward internationalization; outward-inward innovativeness; learning by internatio-nalization; international competitiveness; transition economy